Determinants of the heme-CO vibrational modes in the H-NOX family() - Tran, Rosalie (2011)
The H-NOX family of proteins have important functions in gaseous ligand signaling in organisms from bacteria to humans, including nitric oxide (NO) sensing in mammals, and provide a model system for probing ligand selectivity in hemoproteins. A unique vibrational feature that is ubiquitous throughout the Heme-Nitric oxide/OXygen binding (H-NOX) family is the presence of a high C-O stretching frequency. To investigate the cause of this spectroscopic characteristic, the Fe-CO and C-O stretching frequencies were probed in the H-NOX domain from Thermoanaerobacter tengcongensis (Tt H-NOX) using resonance Raman (RR) spectroscopy. Four classes of heme pocket mutants were generated to assess the changes in stretching frequency: (i) the distal H-bonding network, (ii) the proximal histidine ligand, (iii) modulation of the heme conformation via Ile-5 and Pro-115, and (iv) the conserved Tyr-Ser-Arg (YxSxR) motif. These mutations revealed important electrostatic interactions that dampen the back-donation of the Fe(II) d(π) electrons into the CO π* orbitals. The most significant change occurred upon disruption of the H-bonds between the strictly conserved YxSxR motif and the heme propionate groups, producing two dominant CO-bound heme conformations. One conformer was structurally similar to Tt H-NOX WT; whereas the other displayed a decrease in ν(C-O) of up to ~70 cm(−1) relative to the WT protein, with minimal changes in ν(Fe-CO). Taken together, these results show that the electrostatic interactions in the Tt H-NOX binding pocket are primarily responsible for the high ν(C-O) by decreasing the Fe d(π) → CO π* back-donation, and suggest that the dominant mechanism by which this family modulates the Fe(II)-CO bond likely involves the YxSxR motif.